2015
DOI: 10.4314/jab.v87i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Détection biologique des résidus d’antibiotiques dans le lait et produits laitiers de vache consommés à Ouagadougou, Burkina Faso.

Abstract: 8106positive for aminoglycosides and/or quinolones and/or macrolides (17.24%) and beta-lactam and/or sulfonamides and/or tetracyclines (51.72%). Residues of aminoglycosides and/or quinolones and/or macrolides were detected in 25% of curds, 2.38% of pasteurized milk and 16.66% of yoghurt while, the residues of beta-lactam and/or sulfonamides and/or tetracyclines were detected in 70% of curds, 66.66% of pasteurized milk and 38.88% of yoghurt. Conclusion and Application: Milk and dairy products are contaminated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Because of this mode of diffusion, the ESBLs constitute a significant threat for the countries of West Africa where `the weak socio-economic conditions result in poor hygienic conditions, promoting the spread of resistance. Indeed, most of the farms in Burkina Faso are mainly traditional with unhygienic practices [ 27 ]. Furtheremore, our previous study reported that the people in households mainly use well water as a source of drinking [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this mode of diffusion, the ESBLs constitute a significant threat for the countries of West Africa where `the weak socio-economic conditions result in poor hygienic conditions, promoting the spread of resistance. Indeed, most of the farms in Burkina Faso are mainly traditional with unhygienic practices [ 27 ]. Furtheremore, our previous study reported that the people in households mainly use well water as a source of drinking [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main economic activities in these communities are subsistence farming, animal husbandry and commercial activities [4]. Abuse of antibiotics use in animal husbandry has been highlighted in the country with prevalences of antimicrobial residues of 31% and 51.72% in meat and raw milk, respectively [27,28]. Although antimicrobial use for animals is under veterinary prescription control in Burkina Faso, farmers still use unprescribed antimicrobials as growth promoters or treatment for cattle, poultry and swine [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Because of this mode of diffusion, the ESBLs constitute a signi cant threat for the countries of West Africa where `the weak socio-economic conditions result in poor hygienic conditions, promoting the spread of resistance. Indeed, most of the farms in Burkina Faso are mainly traditional with unhygienic practices [27]. Furtheremore, our previous study reported that the people in households mainly use well water as a source of drinking [34].…”
Section: Discussionmentioning
confidence: 99%
“…The main economic activities in these communities are subsistence farming, animal husbandry and commercial activities [4]. Abuse of antibiotics use in animal husbandry has been highlighted in the country with prevalences of antimicrobial residues of 31% and 51.72% in meat and raw milk, respectively [27,28]. Although antimicrobial use for animals is under veterinary prescription control in Burkina Faso, farmers still use unprescribed antimicrobials as growth promoters or treatment for cattle, poultry and swine [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…These results could be explained by milking conditions in farms, and handling conditions during selling of milk. In fact, Bagré et al (2015) showed that a majority of farms in Burkina Faso are mainly traditional with unhygienic practices. In these farms, 43.9% do not clean udders before milking, with a calabash being the main collection utensil.…”
Section: Prevalence Of E Coli In Dairy Productsmentioning
confidence: 99%